ЦІНА І ЇЇ РОЛЬ В МАРКЕТИНГОВОМУ КОМПЛЕКСІ - Kalinichenko, Olena (Zhytomyr Ivan Franko State University, 2024)
The article considers the main objectives of marketing pricing policy. It is found that by properly developing marketing pricing policy, companies can form their strategic direction, establish relationships with consumers and improve the conditions for the sale of goods, which is an important part of the marketing-mix complex in the marketing management system. Price in the market economy is of key importance, because it is not only a means of exchange, but also an important mechanism affecting the production, distribution, exchange and consumption of goods and services. In the article on the basis of a number of works of domestic and foreign economists, as well as a number of legislative acts in force in our country, the definition of the concept of ‘price’ is given. It is determined that the price affects both the volume of product sales in the domestic and foreign markets and the level of profitability of the firm. It is found out that the main objectives of the firm in the context of pricing are to increase market share, strengthen financial condition, positioning of its products, sales promotion and influence on the behaviour of competitors. Firms may use pricing to realise individual objectives, such as keeping prices low to deter new competitors or to set prices in line with competitors' prices to ensure market stabilisation. Pricing can be used as a tool to maintain brand loyalty, to maintain business relationships with resellers, or as a measure to counter government regulation Prices can be temporarily reduced to promote a product or to attract new customers. Pricing for certain types of goods may be designed to stimulate sales of other goods within the same product mix, using it as a strategy to achieve the firm's long-term goals. It is proved, in marketing, pricing depends on the interaction of three subjects: seller, buyer and competitor, so special attention is paid to the analysis of external factors. The role of factor analysis in the development of marketing pricing policy comes down to the fact that the set price should recover costs and reflect the usefulness of the product or service for the consumer, as well as take into account the competitive situation in the market. Selecting and developing a pricing policy for a company is a complex and comprehensive process that requires an analytical approach, in-depth knowledge of the market situation and flexibility in decision-making. Pricing should be an integrated part of the overall business strategy to achieve long-term goals. In this article, we will look at the pricing process, which consists of six steps, each with its own unique purpose and importance. In a market economy, pricing strategy becomes one of the key factors in a company's success. Free competition confirms that every entrepreneur seeks to maximise their profits. In addition to increasing production volumes and entering new markets, an important task is to reduce the costs of production and sales.